Dyadic Association between Sexual Dysfunction and Sexual Satisfaction: A Cross-Sectional Survey of Heterosexual Couples in Hong Kong. Issue 4 (3rd May 2021) - Wei, Qingong; Zhang, Huiping; Fan, Susan; Yip, Paul
Abstract: Substantial evidence has demonstrated that sexual dysfunction is negatively associated with the sexual satisfaction of individuals in a committed heterosexual relationship. However, little is known about their relationship based on couple data, especially in non-Western societies. We extended this study to examine the extent to which men's and women's sexual dysfunction were associated with their own as well as their partners' sexual satisfaction. Participants were 1, 014 heterosexual couples who participated in a community-based survey in Hong Kong in 2017. Using the actor–partner interdependence model and structural equation modeling, our results indicated that the dyadic model fit the data better than the individual model. Women's orgasm and men's sexual desire functioning were significant predictors of both own and partner's sexual satisfaction, and these two domains had similar effects on the sexual satisfaction of both men and women. These findings are discussed in terms of the importance of taking a dyadic approach to research and enhance sexual health and well-being of heterosexual couples.